2017
DOI: 10.1097/ajp.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

External Validation and Modification of a Predictive Model for Acute Postsurgical Pain at Home After Day Surgery

Abstract: Objectives:In 2009, Gramke and colleagues have described predictive factors to preoperatively detect those at risk for moderate to severe acute postsurgical pain (APSP) after day surgery. The aim of the present study is to externally validate this initial model and to improve and internally validate a modified version of this model.Materials and Methods:Elective patients scheduled for day surgery were prospectively enrolled from November 2008 to April 2010. Model discrimination was quantified using the area un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The positive correlation between postoperative pain and poor QOR has already been suggested in a previous study. A large prospective cohort study found that patient derived expected pain, which is a good predictor of high postoperative pain levels [ 28 ], is also a predictor of poor QOR at POD 4 [ 18 ]. This makes sense as postoperative pain plays a pivotal role in the QOR after surgery and is also known to be closely related with not only the physical status but also socio-cultural, cognitive, psychological and functional dimensions [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between postoperative pain and poor QOR has already been suggested in a previous study. A large prospective cohort study found that patient derived expected pain, which is a good predictor of high postoperative pain levels [ 28 ], is also a predictor of poor QOR at POD 4 [ 18 ]. This makes sense as postoperative pain plays a pivotal role in the QOR after surgery and is also known to be closely related with not only the physical status but also socio-cultural, cognitive, psychological and functional dimensions [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predictive models have been developed to forecast high levels of acute postoperative pain, incorporating questionnaires such as those listed above [49]. Clinical tools to assess preoperative psychological state may not be commonplace in routine practice.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…Although painful surgeries can be performed in an ambulatory setting, the postoperative analgesia after day surgery can become an enormous challenge for patients. Unlike hospital stay which provides the patients specialized personnel, different types of analgesics, and various routes of administration (2,3), home care can have a lot of limitations in terms of the mentioned factors (4). This can explain the high prevalence of acute pain in the first 24 -48 hours after acute day surgery, despite the increased awareness and introduction of multimodal pain therapy strategies over the last decades (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%